1979
DOI: 10.1111/j.1432-1033.1979.tb13109.x
|View full text |Cite
|
Sign up to set email alerts
|

The Hormonal Control of Glycogen Metabolism

Abstract: Inhibitor‐1 has been shown to be phosphorylated in skeletal muscle in vivo. In normal fed animals the degree of phosphorylation was 31 ± 7% and this value increases to 70 ± 12% following an intravenous injection of adrenaline. The results imply that the phosphorylation of inhibitor‐1 may be equally as important as the phosphorylation of phosphorylase kinase in elevating the levels of phosphorylase a. The role of inhibitor‐1 in metabolism is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(46 citation statements)
references
References 21 publications
2
44
0
Order By: Relevance
“…The inhibition reported in table 2 is presumably attributable to both inhibitors, since inhibitor 1 is more abundant in muscle than inhibitor 2 [19] and is normally -3% in the phosphorylated form [22]. Figure 1 indicates that inhibitor 1 is apparently not rapidly dephosphorylated in the presence of a crude muscle extract since its activity was clearly apparent on unpurified preparations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The inhibition reported in table 2 is presumably attributable to both inhibitors, since inhibitor 1 is more abundant in muscle than inhibitor 2 [19] and is normally -3% in the phosphorylated form [22]. Figure 1 indicates that inhibitor 1 is apparently not rapidly dephosphorylated in the presence of a crude muscle extract since its activity was clearly apparent on unpurified preparations.…”
Section: Discussionmentioning
confidence: 98%
“…of a solution containing 4 mM EDTA and 2% trichloroacetic acid, and centrifuged for 5 min at 12 000 rev./ min. The pellet, containing in~bitor 2 [22], was discarded; the supernatant was incubated for 1.5 min in a boiling water bath and centrifuged for 5 min at 12 000 rev./min. The supernatant was filtered on Sephadex G-25, equilibrated with 50 mM glycylglycine (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…Phosphorylase phosphatase I1 was extracted from skeletal muscle as in [7]. The activity of I1 was determined by its ability to inhibit the purified low molecular weight phosphatase.…”
Section: Preparation Of Samples and Assaysmentioning
confidence: 99%
“…In view of high concentration of I1 in skeletal muscle, its high potency as an inhibitor, and control of its activity by phosphorylation, it has been suggested that It may play an important role in the regulation of phosphoprotein phosphatase [2,6,7]. Normal rabbits injected with epinephrine have increased levels of phosphorylated form of I1 [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation